Patients with chronic hepatitis C have circulating cytotoxic T cells which recognize hepatitis C virus-encoded peptides binding to HLA-A2.1 molecules. - Battegay, M (1995)
Antiviral cytotoxic T lymphocytes (CTL) may play a role in clearance of hepatitis C virus (HCV)-infected cells and thereby cause hepatocellular injury during acute and chronic HCV infection. The aim of this study was to identify HLA-A2.1-restricted HCV T-cell epitopes and to evaluate whether anti-HCV-specific CTL are present during chronic hepatitis C. Peripheral blood mononuclear cells from four HLA-A2-positive patients with chronic hepatitis C and from two individuals after recovery from HCV infection were tested against a panel of HCV-encoded peptides derived from different regions of the genome, including some peptides containing HLA-A2.1 binding motifs. HLA-A2-negative patients with chronic hepatitis C as well as healthy HLA-A2-positive (anti-HCV-negative) donors served as controls. Peripheral blood mononuclear cells stimulated repeatedly with several HCV-encoded peptides (three in core, one in NS4B, and one in NS5B) yielded cytolytic responses. All four HLA-A2-positive patients with active infection had CTL specific for at least one of the identified epitopes, whereas two patients who had recovered from HCV infection had almost no CTL responses. Monoclonal antibody blocking experiments performed for two epitopes demonstrated a class I- and HLA-A2-restricted CTL response. CTL epitopes could partially be predicted by HLA-A2 binding motifs and more reliably by quantitative HLA-A2.1 molecule binding assays. Most of the identified epitopes could also be produced via the endogenous pathway. Specific CTL against multiple, mostly highly conserved epitopes of HCV were detected during chronic HCV infection. This finding may be important for further investigations of the immunopathogenesis of HCV, the development of potential therapies against HCV on the basis of induction or enhancement of cellular immunity, and the design of vaccines.